THE METAPHOR OF WOMEN AS HOUSEKEEPERS IN THE LYRICAL PROSE NOVEL PENGAKUAN PARIYEM: The Metaphor of Women as Servants in the Lyric Prose Novel “Pengakuan Pariyem”: A Cognitive Linguistic Study - Latifah Rahmadani Putri; Suhandano (ELOQUENCE : Journal of Foreign Language, 2025)
Background: Women are often trapped in traditional stereotypes, viewed merely as supporters of men, particularly in patriarchal narratives. In this study, metaphors are used to illustrate how people understand and think about a sosial situation. Purpose: This research aims to describe how women as maids are metaphorized. Method: The method used in this study is qualitative descriptive. The data source is sentences containing metaphors included in the novel Pengakuan Pariyem. This study analyzes 35 metaphorical expressions from Linus Suryadi’s Pengakuan Pariyem using Lakoff and Jhonson (2003) conseptual metaphor theory to uncover the representation of women in the Javanese patrichal system. The data source use in this study is literary works using a cognitive approach. Results and Discussion: This study succeeded in finding analogies of women's lives as maids, such as water, animals, flavors, and objects. Physical analogies of women as helpers such as plants, objects, and colors. In addition, metaphors about religion, emotions, thoughts, human relationships, and morality were also found. Conclusions and Implications: The metaphors in the novel describe female characters who do not give up on their lives, even though they are less fortunate.